ولاية العهد من المنظور الفقـــــــــــــــــــــــــــــهي - ضيف الله,عيسى; حمزة,عبد الصمد (University of Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة إلى إلقاء الضوء على قضية هامة تتعلق بنظام الحكم في الإسلام، وترتبط ارتباطاً وثيقاً بمستقبل الحكم واستمراره في الدولة الإسلامية، وهي قضية ولاية العهد التي أثارت جدلاً واسعاً بين العلماء والفقهاء حول مشروعيتها وصحتها، وقد تبيّن من خلال هذا البحث مدى اجتهاد فقهاء السياسة الشرعية في هذه المسألة ومحاولة تكييف الواقع التاريخي وتطورات النظام السياسي وفق الفقه الإسلامي، وقد أقرّ غالبية هؤلاء الفقهاء على جوازها إذا استوفت جميع شروط صحتها، كما أجمعوا على عدم جواز التوريث في منصب الخلافة.This study aims to shed light on an important issue related to the system of governance in Islam, which is closely linked to the future and continuity of governance in the Islamic state. It revolves around the issue of the "Wilayat al-Ahd" (succession) that has sparked wide-ranging debates among scholars and jurists regarding its legitimacy and validity. Through this issue, it becomes apparent the extent of the exertion by scholars of political jurisprudence in this matter and their attempt to adapt historical realities and political system developments in accordance with Islamic jurisprudence. These scholars have unanimously agreed on the permissibility of establishing the caliphate through succession if all the necessary conditions are met, while also acknowledging the impermissibility of hereditary succession in the position of the caliphate.
Keywords: السياسة الشرعية; الفقه الإسلامي; الفقهاء; الاستخلاف; Wilayat al-Ahd; succession; political jurisprudence; Islamic jurisprudence; scholars; ولاية العهد